Language and verbal skills - Virginia Association for Retarded Citizen, Inc.; Virginia Commonwealth University; Central Virginia Educational Television (Columbus, Ohio : Charles E. Merrill Pub. Co., 1976)
Distiguishes between receptive and expressive language in the developmentally disable child. Also focusses on inner language and some aspects of non-verbal language
Keywords: Handicapped children -- Education; Developmentally disabled children -- Language